Answer:
y = -2(x+2)(x-1)/((x+3)(x-6)) = (-2x^2 -2x +4)/(x^2 -3x -18)
Step-by-step explanation:
A polynomial function will have a zero at x=a if it has a factor of (x-a). For the rational function to have zeros at x=-2 and x=1, the numerator factors must include (x+2) and (x-1).
For the function to have vertical asymptotes at x=-3 and x=6, the denominator of the rational function must have zeros there. That is, the denominator must have factors (x+3) and (x-6). Then the function with the required zeros and vertical asymtotes must look like ...
f(x) = (x+2)(x-1)/((x+3)(x-6))
This function will have a horizontal asymptote at x=1 because the numerator and denominator degrees are the same. In order for the horizontal asymptote to be -2, we must multiply this function by -2.
The rational function may be ...
y = -2(x +2)(x -1)/((x +3)(x -6))
If you want the factors multiplied out, this becomes
y = (-2x^2 -2x +4)/(x^2 -3x -18)
Answer: Ashley had more yarn, 1 yard = 3 ft 3 times 4 = 12 so 3 yards is 12 feet.
Step-by-step explanation:
you can't really see the question it's too blurry
Answer:
The correct answer would be 2:1
Step-by-step explanation:
In order to find this, start with the ratio as it is written and sub in the values. Then simplify to the lowest possible terms.
Ran:Walker
8:4
2:1